The Effects of Climate Variation on Fisheries and Coastal Aquaculture - Nedtharnn, Urairathr (Journal of Fisheries and Environment, 2015)
The two-part study was conducted to ascertain the effect of climate variation on growth of key aquaculture species, i.e. mud crab raised as soft-shell crab, and phytoplankton, a key food source for shellfish. Data were collected from the districts Khlung, Laemsing and Thamai, Chantaburi Province, Thailand, using structured questionnaire, to determine the effect of climate variation on coastal fisheries. The first part of the study showed that sea temperature could significantly alter the growth rates of both mud crab and phytoplankton (p<0.05). The optimal temperature for mud crab growth was between 30 and 33oC, whereas growth rate of phytoplankton was highest with a shortest doubling time at 30oC. However, if the temperature exceeded 32oC, plankton population decreased with the rate declining with cascading effects on shellfish growth. The second part of the study revealed that fishers and aquaculture farmers perceived that climate variation affected their livelihoods including fisheries and aquaculture production. These climate variations included raining during non-rainy season, increased rain fall, severe waves, and changes in monsoon timing. In order to deal with climate variation events, fishing communities should listen to news regarding the weather before making decisions and should exchange information within their communities. Additionally, the government should develop an effective method for forecasting weather, rainfall, and freshwater runoff, and communication channels should be improved.